Hubungan masa kerja, beban kerja, dan stres kerja dengan kelelahan kerja pada tenaga non medis di rumah sakit - Eka Andini Putri; Willia Novita Eka Rini; Adelina Fitri; Budi Aswin Sanrus (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Occupational fatigue is a condition of decreased physical and mental capacity that can impact productivity and workplace safety. Non-medical staff in hospitals are at risk of experiencing fatigue due to administrative work demands, workload, and psychological stress. Purpose: To determine the relationship between length of service, workload, and job stress with job fatigue in non-medical staff. Method: This study used an observational analytical design with a cross-sectional approach. The sample in this study was 149 non-medical staff at Sekayu Regional Hospital. The sampling technique used accidental sampling. Data analysis was performed using the Chi-square test with a significance level of 0.05. Results: There was a relationship between length of service, workload, and job stress with job fatigue. Respondents with long tenure, high workload, and high job stress tended to experience more severe job fatigue. Conclusion: Length of service, workload, and job stress are associated with job fatigue in non-medical staff at Sekayu Regional Hospital.   Keywords: Length Of Service; Work Fatigue; Work-Related Stress; Workload.